(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article provides information on feeding, keeping and caring for young female calves. Activities that are carried out from the first birth period of calves and aspects that should be taken into account in feeding them are described.